Single-cell insights into transcriptomic diversity in immunity. Issue 5 (October 2017) - Miragaia, Ricardo J.; Teichmann, Sarah A.; Hagai, Tzachi
Abstract: Our body is composed of a diverse set of cells that together perform numerous functions in a highly coordinated manner, allowing a timely response to external cues and to inter-cellular signals. Emerging single-cell technologies enable investigation of these intricate processes at an unprecedented level. Here, we discuss recent work on cellular differentiation and heterogeneity, and describe novel experimental and computational tools that enable this research. As an example of cellular differentiation, we focus on T cell development in response to diverse infections and in immune pathologies. We then describe how single-cell studies have contributed to our understanding of transcriptional variability in innate immune response, and how this variability might be important in achieving a balanced immune response. Future single-cell studies will likely include spatial analyses and lineage tracing strategies, holding great potential to further our understanding of cell behaviour in steady-state and pathological conditions. Highlights: Novel single-cell approaches enable high-resolution profiling of important cellular processes. Cell differentiation processes in immune cells can be studied to infer detailed stages of differentiation and maturation New techniques allow exploration of cellular heterogeneity and its physiological importance in innate immunity